Hematological Causes of Venous Thrombosis in Young People: High Incidence of Myeloproliferative Disorder as Underlying Disease in Patients with Splanchnic Venous Thrombosis - Teofili, Luciana; De Stefano, Valerio; Leone, Giuseppe; Micalizzi, Paola; lovino, Michela Stefania; Alfano, Generoso; Bizzi, Bruno (Thrombosis and Haemostasis, 1992)
Thrombotic events occur frequently in myeloproliferative disorders, namely polycythaemia vera and essential throm-bocythaemia. Standard diagnostic criteria are designed quite stringent, so that a number of patients could be underdiagnosed. Spontaneous erythroid colonies formation from bone marrow or peripheral blood in the absence of exogenous erythropoietin is considered a reliable index of myeloproliferative disorder even at early stages. Endogenous erythroid colonies (EECs) formation was assessed in 43 patients having recently suffered from venous thrombosis prior to 45 years and without a previous diagnosis of hematological disease favouring thrombosis. A screening for coagulative abnormalities associated with thrombophilia was also carried out: in 5 patients (11.6%) a plasmatic thrombogenic defect was found (quantitative deficiency of antithrombin III, 1 case, protein C, 2 cases, protein S, 1 case, and plasminogen, 1 case). In 10 patients (2 males and 8 females) (23.2%) EECs assay was positive, allowing diagnosis of myeloproliferative disease even though 7 of them did not fulfill standard diagnostic criteria. In the other 3 patients who met the criteria for diagnosis of overt myeloproliferative disease the thrombotic event was the inaugural manifestation. In all these EECs-positive patients thrombosis involved mesenteric and portal veins (n = 4), hepatic veins (n = 3), portal vein (n = 2), mesenteric vein (n = 1). One of them was simultaneously affected from congenital protein C deficiency. Thus latent or atypical forms of myeloproliferative disease as well as the overt stages were the most frequent recognized cause of splanchnic venous thrombosis, accounting for 55% of the cases of our series. On the contrary no EECs-positive subject was found among the 25 patients with other sites of thrombosis. It is concluded that a myeloproliferative disorder should be carefully considered in young patients with splanchnic venous thrombosis and a thorough investigation should include evaluation of EECs.